A comparative survey on lightweight block ciphers for resource constrained applications. (5th February 2020) - Singh, Pulkit; Acharya, Bibhudendra; Chaurasiya, Rahul Kumar
Information security for low-resource devices has received a fair amount of attention in recent years. These devices have physical constraint in terms of area, power, and memory. Therefore, lightweight cryptographic algorithms are providing sufficient security to such devices. In this paper, many lightweight block ciphers have been comprehensively discussed with their characteristics. These ciphers are broadly categorised based on structural design of round function. In addition, the analysis indicates that few lightweight ciphers are well-suited for hardware implementation. Few are healthy compatible with software implementation. However, some of the block ciphers are designed well for both hardware and software implementations. Moreover, there are various performance metrics used for comparison in resource constrained environments (RCEs). More specifically, the objective of this survey is to compare various modern symmetric cryptographic solutions employed to secure small-scale communication devices.